Menggagas Metodologi Hukum Islam Masa Depan: Kajian Tentang Rekonstruksi Usul al-Fiqh - Ulfah, Isnatin (Justicia Islamica, 2009)
This study aims to initiate a future Islamic legal methodology through a critical study of the reconstruction of the principles of fiqh. The method used is qualitative with a historical-philosophical approach, through an analysis of the development of classical principles of fiqh and its response to the challenges of modern times. The results of the study show that the traditional framework of usul al-fiqh, which is largely influenced by theological and scholastic mindsets, needs to be reconstructed to be more adaptive to contemporary social, political, and cultural dynamics. This reconstruction includes renewing the ijtihad paradigm, strengthening the maqashid Syariah approach, and integrating it with social sciences. This study emphasizes that the methodological renewal of usul al-fiqh is a strategic step towards making Islamic law more contextual, relevant, and solution-oriented in addressing the problems of the ummah in the future.